2012
DOI: 10.1155/2012/675361
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of AflatoxinogenicAspergillus parasiticusin Jordan

Abstract: Aflatoxins are potent carcinogens and produced by almost all Aspergillus parasiticus isolates and about 35% of Aspergillus flavus isolates. Chemical methods are used for detection of aflatoxins in food and feed. These methods cannot detect aflatoxinogenic fungi in samples, which contain undetectable amounts of aflatoxins. The objective of this research work was to ascertain the importance of molecular and microbiological methods in detection of aflatoxinogenic fungus A. parasiticus in food and feed samples in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…According to Abbas (2005), high amount of moisture allows the growth of fungal species. Al-Hmoud et al (2012) demonstrated the incidence of fungi in the food and feed samples and showed a wide variation that was in the range of 0.2x10 2 − 2.4x10 4 cfu/g. Similarly, Egbuta et al (2015) reported a range of filamentous fungi including Aspergillus, Penicillium, Fusarium, etc., contaminating the food commodities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Abbas (2005), high amount of moisture allows the growth of fungal species. Al-Hmoud et al (2012) demonstrated the incidence of fungi in the food and feed samples and showed a wide variation that was in the range of 0.2x10 2 − 2.4x10 4 cfu/g. Similarly, Egbuta et al (2015) reported a range of filamentous fungi including Aspergillus, Penicillium, Fusarium, etc., contaminating the food commodities.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that A. niger produces Ochratoxin A, but not aflatoxins (Schuster et al, 2002). Al-Hmoud et al (2012) has demonstrated the prevalence of aflatoxinogenic A. parasiticus through PCR in food and feed samples in Jordan. In addition, real-time PCR (RT-PCR) method directed against the nor-1 gene of the aflatoxin biosynthetic pathway as target sequence was also used to scan Aspergillus flavus population in peanuts (Passone et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A. parasiticus , on the other hand, is more host‐specific with a high affinity for peanuts (Kumar et al., 2017). Almost all known strains of A. parasicticus are toxigenic and produce other metabolites, including kojic acid and aspergillic acid (Al‐Hmoud et al., 2012). It produces both B‐ and G‐series of aflatoxin (Martins et al., 2017).…”
Section: Fungal Producers Of Aflatoxinmentioning
confidence: 99%
“…Chemical methods like chromatographic methodsare used for detection of aflatoxin B1 in contaminated food and feed. However, these methods cannot detect aflatoxinogenic fungi in contaminated samples which contain undetectable amounts of aflatoxins [7]. Therefore we can use an excellent and direct methods like reverse transcription -polymerase chain reaction (RT-PCR) which has been devised as a method of RNA amplification and quantification after its conversion to cDNA.…”
Section: Introductionmentioning
confidence: 99%